Kajian Beberapa Sifat Fisik Tanah Entisol yang Mengandung Residu Biochar dan Kompos pada Tumpang Sari Jagung (Zea mays L.) dan Kacang Nasi (Vigna angularis L.) - Maria Krisanti Moru (Savana Cendana, 2021)
The purpose of this study is to identify some of the physical properties of the entisol ground that contain biochar residue on the corn cider (Zeamays L.) and rice beans (Vigna Angularis L.) and to identify the most optimal types of biochar and compost residue on some of the entisol’s properties by containing the biochar and compos residue on the corn (Zeamays L) and rice beens (Vign a Angularis L.) the study carried out in july 2020-september 2020 on the agricultural farm, Timor university kefamenanu – Timor Tengah Utara. The design used in research is a random grouping of two vectored areas. The first factor is the biochar residue consisting of four cedars, which is without biochar, 5 tons/acre wheat chaff, five tons/ acre are biochar, five tons/acre views, biochar kerinyu 5 tons/ acre wheat, the second factor of compost residu consist of two levels without compost, 0 tons/acre are, compost ten tons/acres are. There’s an interaction between duchar and residue compost residual treatment on final ground temperature observations. The biochar sakam rice residue is capable of optimize the physical properties of the soil as shown by highest density of the original soil and the lowest volume of soil. Though it does not make a noticeable impact between treatment, the compost residue does increase the physical quality of the soil.